Bacteriophages as surface and ground water tracers - Rossi, Pierre; Dörfliger, Nathalie; Kennedy, Keith; Müller, Imre; Aragno, Michel (My University, 1998)
Bacteriophages are increasingly used as tracers for quantitative analysis in both hydrology and hydrogeology. The biological particles are neither toxic nor pathogenic for other living organisms as they penetrate only a specific bacterial host. They have many advantages over classical fluorescent tracers and offer the additional possibility of multi-point injection for tracer tests. Several years of research make them suitable for quantitative transport analysis and flow boundary delineation in both surface and ground waters, including karst, fractured and porous media aquifers.
This article presents the effective application of bacteriophages based on their use in differing Swiss hydrological environments and compares their behaviour to conventional coloured dye or salt-type tracers. In surface water and karst aquifers, bacteriophages travel at about the same speed as the typically referenced fluorescent tracers (uranine, sulphurhodamine G extra). In aquifers of interstitial porosity, however, they appear to migrate more rapidly than fluorescent tracers, albeit with a significant reduction in their numbers within the porous media. This faster travel time implies that a modified rationale is needed for defining some gro und water protection area boundaries. Further developments of other bacteriophages and their documentation as tracer methods should result in an accurate and efficient tracer tool that will be a proven alternative to conventional fluorescent dyes.